2017
DOI: 10.3389/fmicb.2017.01452
|View full text |Cite
|
Sign up to set email alerts
|

Watershed Urbanization Linked to Differences in Stream Bacterial Community Composition

Abstract: Urbanization strongly influences headwater stream chemistry and hydrology, but little is known about how these conditions impact bacterial community composition. We predicted that urbanization would impact bacterial community composition, but that stream water column bacterial communities would be most strongly linked to urbanization at a watershed-scale, as measured by impervious cover, while sediment bacterial communities would correlate with environmental conditions at the scale of stream reaches. To test t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 98 publications
8
60
6
Order By: Relevance
“…These results are in contrast with widely reported decreases in the diversity of ciliate, macroinvertebrate and fish communities in urban streams (Helms et al, 2005;Moore and Palmer, 2005;Lear et al, 2011). This finding is consistent with the hypothesis recently put forward by Hosen et al, (2017), who suggested that similar levels of bacterial diversity are maintained across the urbanization gradient because the introduction of novel bacterial taxa from sewage, water distribution or septic systems, and stormwater may compensate for the loss of taxa sensitive to urban conditions.…”
Section: Low Levels Of Watershed Urbanization Alter Sediment Bacteriasupporting
confidence: 89%
“…These results are in contrast with widely reported decreases in the diversity of ciliate, macroinvertebrate and fish communities in urban streams (Helms et al, 2005;Moore and Palmer, 2005;Lear et al, 2011). This finding is consistent with the hypothesis recently put forward by Hosen et al, (2017), who suggested that similar levels of bacterial diversity are maintained across the urbanization gradient because the introduction of novel bacterial taxa from sewage, water distribution or septic systems, and stormwater may compensate for the loss of taxa sensitive to urban conditions.…”
Section: Low Levels Of Watershed Urbanization Alter Sediment Bacteriasupporting
confidence: 89%
“…Contrary to our expectations (Perryman et al 2008, Wang et al 2011, Hosen et al 2017, microbial communities, as measured by OTU richness and community composition, did not shift perceptibly along the development gradient. The 2 denitrifier functional genes we measured with T-RFLP indicated that some community members responded to temperature (nirK) or to substrate supply and contamination (nosZ) because these variables were correlated with the major axes of variation in composition.…”
Section: Discussioncontrasting
confidence: 99%
“…* 5 p < 0.05, ** 5 p < 0.01, *** p < 0.001, NS 5 not significant. fects of urban hydrology and water quality on microbial community composition still are not well understood (Hosen et al 2017). In a synthesis of lotic microbial diversity studies, Zeglin (2015) found that microbial diversity was negatively affected by metals, temperature, substrate type, or hydrology more commonly than by more general effects of land use or nutrient concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Localized sorting of aquatic bacterial communities in response to changes in water physiochemical properties has been previously reported (Moss, 2008 ; Hu et al, 2014 ; Sangchan et al, 2014 ; Staley et al, 2015 ; Van Rossum et al, 2015 ; Borges et al, 2017 ; Hosen et al, 2017 ). Jurelevicius et al ( 2013 ) demonstrated that different Proteobacteria (e.g., Achromobacter spp.)…”
Section: Introductionmentioning
confidence: 83%